Measurement of multimode fibre length and attenuation using meos optical time domain reflectometer setup - 509578 Mutia Suhaibah Abdullah; Abdul Rahim Omar; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains (Fizik Kesihatan)) - Universiti Teknologi Malaysia, 2007